ответ:
объяснение:
интуиция мне подсказывает, что требуетс это:
1/(6а-4b) - 1/(6a+4b) + 3a/(9a^2 - 4b^2)
т. к.
6a-4b = 2*(3a-2b)
6a+4b = 2*(3a+2b)
9a^2 - 4b^2 = (3a-2b)(3a+2b) - разность квадратов
то общим знаменателем дроби будет 2(3a-2b)(3a+2b)
в числителе дроби будет:
2(3a+2b) + 2(3a-2b) + 2*3a = 6a + 4b + 6a - 4b + 6a = 18a
дробь окончательно:
18a/2(3a-2b)(3a+2b) = 9a/(9a^2 - 4b^2)
ответ:
9а
9a^2 - 4b^2
2sinxcosx-√3cosx=0
cosx(2sinx-√3)=0
cosx=0⇒x=π/2+πn,n∈Z
sinx=√3/2⇒x=(-1)^n*π/3+πk,k∈Z
б)sin 2x=√2 cos x
2sinxcosx-√2cosx=0
cosx(2sinx-√2)=0
cosx=0⇒x=π/2+πn,n∈Z
sinx=√2/2⇒x=(-1)^n*π/4+πk,k∈Z в)sin(0,5п+x)+ sin 2x=0
г)cos(0,5п+x)+ sin 2x=0
-sinx+2sinxcosx=0
-sinx(1-2cosx)=0
sinx=0⇒x=πn,n∈Z
cosx=1/2⇒x=+-π/3+2πk,k∈Z
д)sin 4x+√3 sin 3x+sin 2x=0
2sin3xcosx+√3sin3x=0
sin3x(2cosx+√3)=0
sin3x=0⇒3x=πn,n∈Z⇒x=πn/3,n∈Z
cosx=-√3/2⇒x=+-5π/6+2πk,k∈Z
е)cos 3x+sin 5x=sin x
cos3x+sin5x-sinx=0
cos3x+2sin2xcos3x=0
cos3x(1+2sin2x)=0
cos3x=0⇒3x=π/2+πn,n∈Z⇒x=π/6+πn/3,n∈Z
sin2x=-1/2⇒2x=(-1)^(k+1)*π/6+πk,k∈Z⇒x=(-1)^(n+1)*π/12+πk/2,k∈Z